Test video files - Larsson, Joakim (Swedish National Data Service, 2023)
Abc

Abc
Test videofiler
Keywords: Agricultural and aquaculture facilities; Jordbruks- och vattenbruksanläggningar; Buildings; Byggnader; Coordinate reference systems; Referenskoordinatsystem; abstract character; abstrakthet; events and action; händelser och handling; objects; entiteter; role; roll (uppgift); Morbidity and mortality; Morbiditet och mortalitet; ECONOMICS; EKONOMI; Economic systems and development; Ekonomiska system och ekonomisk utveckling; Mathematical Analysis; Matematisk analys; Algebra and Logic; Algebra och logik; Probability Theory and Statistics; Sannolikhetsteori och statistik; Geoscientific Information; Geovetenskap; Health; Hälsa; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Environment; Miljö